2010
DOI: 10.5424/sjar/2010082-1184
|View full text |Cite
|
Sign up to set email alerts
|

Competition of velvetleaf (Abutilon theophrasti M.) weed with cotton (Gossypium hirsutum L.). Economic damage threshold

Abstract: The effect of the weed Abutilon theophrasti M. (common name: velvetleaf) on the growth of cotton grown in the Guadalquivir Valley, was studied by examining the influence of weed density on growth of the weed and that of cotton. Velvetleaf impeded normal cotton growth caused production losses as a result of the stress the cotton was subjected to. Additionally there was competition among velvet leaf plants at high velvet leaf densities. The influence  of velvetleaf density in coexistence with cotton has been als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
5
12
0
Order By: Relevance
“…In trend comparison, only linear trend was significant. These results confirm the findings of Cortes et al (2010). They observed a linear increase in dry weight (kg m The same trend was observed by Morales-Payan, (2000), who reported that weed dry biomass was increased linearly as parthenium plant densities were increased 1 to 13 plants m …”
Section: Growth and Nutrient Uptake Of P Hysterophorus Parthenium Drsupporting
confidence: 90%
“…In trend comparison, only linear trend was significant. These results confirm the findings of Cortes et al (2010). They observed a linear increase in dry weight (kg m The same trend was observed by Morales-Payan, (2000), who reported that weed dry biomass was increased linearly as parthenium plant densities were increased 1 to 13 plants m …”
Section: Growth and Nutrient Uptake Of P Hysterophorus Parthenium Drsupporting
confidence: 90%
“…Redroot pigweed at high densities resulted in strong shading of the cotton plants and prevented them from reaching their typical height; this is consistent with the competitive effect of velvetleaf ( Abutilon theophrasti ) on cotton observed by Cortés et al . [ 36 ]. The impact of increasing weed densities on the stem diameters followed similar trend in both cotton and redroot pigweed.…”
Section: Resultsmentioning
confidence: 99%
“…Velvetleaf is now a common and troublesome weed in several crops such as maize (Zea mays L.) (Lindquist et al, 1996;McDonald et al, 2004), soybean [Glycine max (L.) Merr.] (Akey et al, 1991;Begonia et al, 1991;Ziska, 2012), cotton (Gossypium hirsutum L.) (Cortés et al, 2010), and grain sorghum [Sorghum bicolor (L.) Moench] (Traoré et al, 2003). In recent decades, velvetleaf has become an increasingly problematic weed in cotton field in central China (Ma et al, 2016).…”
mentioning
confidence: 99%